1983
DOI: 10.3109/10826088309027366
|View full text |Cite
|
Sign up to set email alerts
|

The Alcoholic Stigma and the Disease Concept

Abstract: Acceptance by the client of the label "alcoholic" is viewed by many practitioners as a prerequisite to alcohol abuse recovery. This study demonstrates, however, that the label is a highly stigmatized term associated with the skid row habitué. The 1956 American Medical Association acceptance of alcoholism as within the "purview of medical practice" was an important step for those who believed alcoholism could be destigmatized under the disease label. This study demonstrates that although the disease concept is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
1
22
2
3
Order By: Relevance
“…In fact, both views, i.e. seeing alcohol dependence as an illness and blaming those affected for it, have been stated simultaneously by many respondents [14,16,17,18,20,21]. Although findings from previous studies are quite consistent, exact numbers are difficult to compare because the different types of study populations and survey methodologies have led to a wide range of results.…”
Section: Introductioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In fact, both views, i.e. seeing alcohol dependence as an illness and blaming those affected for it, have been stated simultaneously by many respondents [14,16,17,18,20,21]. Although findings from previous studies are quite consistent, exact numbers are difficult to compare because the different types of study populations and survey methodologies have led to a wide range of results.…”
Section: Introductioncontrasting
confidence: 39%
“…However, population surveys conducted in the USA and Europe since then have demonstrated that the illness concept of alcohol dependence has only partially permeated public opinion (see [14,15,16,17,18,19,20] for examples). Furthermore, defining alcohol dependence as an illness does not prevent blaming the affected individual.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different types of diseases, which are associated with varying levels of stigma. For example, people generally take a more sympathetic view toward cancer or Type 1 diabetes than alcoholism, Type 2 diabetes, or mental illness (Dean and Poremba, 1983). Therefore, it is not obvious that people will react to the disease label in the way the AMA intends.…”
Section: Introductionmentioning
confidence: 98%
“…One study revealed that individuals who more strongly endorse social or behavioral causes for alcoholism were likely to report lower personal consumption [Tolor and Tamerin, 1975]. Another study found 58% of participants from the general population endorsed the disease or medical model of alcoholism [Dean and Poremba, 1983]. However, when asked to describe their views of alcoholics, respondents still chose negative stigmatizing descriptors that indicated some belief in a social or behavioral model.…”
Section: Introductionmentioning
confidence: 99%